Sensory nerves in the spotlight of the stem cell niche - Picoli, Caroline C. (Stem Cells Transl Med, 2020)
Niches are specialized tissue microenvironments that control stem cells functioning. The bone marrow mesenchymal stem cell niche defines a location within the marrow in which mesenchymal stem cells are retained and produce new cells throughout life. Deciphering the signaling mechanisms by which the niche regulates stem cell fate will facilitate the use of these cells for therapy. Recent studies, by using state‐of‐the‐art methodologies, including sophisticated in vivo inducible genetic techniques, such as lineage‐tracing Cre/loxP mediated systems, in combination with pharmacological inhibition, provide evidence that sensory neuron is an important component of the bone marrow mesenchymal stem cell niche. Strikingly, knockout of a specific receptor in sensory neurons blocked stem cell function in the bone marrow. The knowledge arising from these discoveries will be crucial for stem cell manipulation in the future. Here, we review recent progress in our understanding of sensory nerves biology in the stem cell niche.